STRATEGI PENINGKATAN KESIAPAN APARATUR PEMERINTAH KOTA BOGOR DALAM IMPLEMENTASI SISTEM INFORMASI PENGELOAAN KEUANGAN DAERAH - Sumaryanto, Sumaryanto; Falatehan, A. Faroby; Rachmina, Dwi (Jurnal Manajemen Pembangunan Daerah, 2017)
ABSTRACTUtilization of information technology in all stages of local financial management becomes very important especially in the effort to bring out good governance. Local financial management must be implemented in an orderly manner and in accordance with law, efficient, effective, transparent, accountable and responsible with due regard to justice, compliance and benefit to the community. The purposes of this research were to analyze the stage of employee readyness in implementation of local financial management information system, to analyze the effectivity of local financial management information system in Goverment Internal Controlling System and to obtain the strategy improving employee-readiness of Bogor City goverment in implementation of local financial management information system. The data consisted of primary and secondary data. Primary data was obtained from direct observation, interview and questioners with stratified random sampling method. While the secondary data was obtained from literature and related documents. This study used rating scale analysis, and SWOT analysis. The Result of study showed that employee-readiness of Bogor City goverment in implementation of local financial manangement information system were on the ready criteria but still needed a little improvement, and local financial management information system were quite effective to assist financial management employee in Bogor City goverment in implementation of Goverment Internal Controlling System. The chosen strategy was to improve the development and capacity building of competency-based employees in local financial management.Key words :   employee-readiness, financial, information system, strategy.ABSTRAKPemanfaatan teknologi informasi pada setiap tahapan pengelolaan keuangan daerah menjadi sangat penting terutama dalam upaya mewujudkan tata kelola pemerintahan yang baik. Pengelolaan keuangan daerah harus dilaksanakan scara tertib, sesuai dan taat tterhadap peraturan perundang-undangan, sfektif, efisien, transparan, akuntabel, bertanggung jawab dengan memperhatikan keadilan, kepatuhan dan bermanfaat bagi masyarakat. Penelitian ini bertujuan menganalisis tingkat kesiapan aparatur dalam implementasi sistem informasi pengelolaan keuangan daerah di Lingkungan Pemerintah Kota Bogor, menganalisis efektifitas sistem informasi pengelolaan keuangan daearah dalam pelaksanaan Sistem Pengendalian Intern di Lingkungan Pemerintah Kota Bogor dan merumuskan strategi yang dapat dilakukan untuk meningkatkan kesiapan aparatur Pemerintah Kota Bogor dalam implementasi sistem informasi pengelolaan keuangan daerah. Data yang digunakan adalah data primer dari dan data sekunder. Data primer diperoleh dari observasi, wawancara dan kuesioner dengan metoda stratified random sampling. Sedangkan data skunder diperoleh melalui literatur dan dokumen-dokumen terkait. Penelitian ini menggunakan analisis rating scale dan analisis SWOT. Hasil penelitian menunjukan bahwa, kesiapan aparatur dalam implementasi sistem informasi pengelolaan keuangan daerah secara keseluruhan  berada pada kriteria siap tetapi masih perlu peningkatan dan sistem informasi pengelolaan keuangan daerah cukup efektif dalam penyelenggaraan sistem pengendalian intern pemerintah. Strategi yang terpilih adalah peningkatan pembinaan dan pengembangan kapasitas aparatur pengguna sistem informasi pengelolaan keuangan daerah yang berbasis kompetensi. Kata kunci: kesiapan aparatur, sistem informasi, pengelolan keuangan, strategi.